Organizing forms of the interaction Interior Troops parts and subdivisions when performing routine and combat tasks in crisis situation - Kryvenko О. V. (Honor and Law, 2019)
Organizing forms of the interaction Interior Troops parts and subdivisions when performing routine and combat tasks in crisis situation on real examples routine and combat activity are analysed.